PENGEMBANGAN KETERAMPILAN BERPIKIR KRITIS MELALUI PEMBELAJARAN BERBASIS MASALAH - HAMDAN ROBBANI (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
Critical thinking skills are essential competencies in dealing with the complexities of the 21st century. This research aims to analyze the effectiveness of Problem-Based Learning (PBL) in developing students' critical thinking skills. The method used is a literature study by analyzing literature from books, journals, and trusted articles. The results showed that PBL was able to improve students' ability to analyze problems, evaluate information, and formulate solutions through a collaborative process. The implications of this research emphasize the importance of integrating PBL in the educational curriculum to equip students with critical thinking skills relevant to the needs of the digital era.